2016
DOI: 10.1080/19648189.2016.1177601
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of gypsum–cement foam concrete: effects of surfactant

Abstract: International audienceThe mineral foams studied were mainly composed of a reactive, partially anhydrous calcium sulphate (90%) and Portland cement (10%), mixed with a low water-to-binder ratio (W/B =.35) leading to a highly concentrated suspension. The foaming method used allowed a wide foam density range (250 andlt; ρ andlt; 820 kg/m3) to be obtained after hardening and drying, with the same mineral suspension composition. To ensure that foam formed and remained stable until the material had set, six surfacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 12 publications
0
19
0
2
Order By: Relevance
“…The thermal performance of porous materials has been investigated since the last decade by [ 204 , 205 , 206 , 207 ]. The effect of pozzolan, density, foamer content, aggregate mineralogy and microstructural factors on conductivity are the scope of [ 208 ].…”
Section: Properties Of Frfcmentioning
confidence: 99%
“…The thermal performance of porous materials has been investigated since the last decade by [ 204 , 205 , 206 , 207 ]. The effect of pozzolan, density, foamer content, aggregate mineralogy and microstructural factors on conductivity are the scope of [ 208 ].…”
Section: Properties Of Frfcmentioning
confidence: 99%
“…11 Mechanically foamed gypsum materials usually have poor mechanical properties 12,13 and are mostly used as soundabsorbing materials. Nevertheless, Samson et al 14 found that material with better mechanical properties (up to 2 MPa) can be made with the proper choice of SAS.…”
Section: Introductionmentioning
confidence: 99%
“…The figure clearly indicates that the prepared FAAG in this study is capable of achieving either lower thermal conductivity or higher compressive strength than other existing foamed products. For instance, the FAAG developed in this study outperformed the cement-gypsum binders (Samson et al, 2017), the contaminated dredged river sediment foamed concrete (Yang et al, 2020) and the magnesium phosphate cement-based foamed concrete (Li et al, 2019) in terms of the strength (Figure 11). At the same time, the FAAG also presents slightly higher thermal conductivity but greater strength than some foamed products such as black dustbased autoclaved aerated concrete (Maneewan et al, 2019) and fly-ash based foamed geopolymer (Feng et al, 2015).…”
Section: Thermal Conductivitymentioning
confidence: 85%